Governed through choice : autonomy, technology, and the politics of reproduction - Denbow, Jennifer M. (New York University Press, 2015)
At the center of the "war on women" lies the fact that women in the contemporary United States are facing more widespread and increased surveillance of their reproductive health and decisions. In recent years states have passed a record number of laws restricting abortion. Physicians continue to sterilize some women against their will, especially those in prison, while other women who choose to forego reproduction cannot find physicians to sterilize them. While these actions seem to undermine women's decision-making authority, experts and state actors often defend them in terms of promoting wo